Effetti economici e conseguenze sulla velocità del progresso dell'umanità, delle limitazioni delle nascite. - Ginatta, Marco Vincenzo (Studia Bioethica, 2013)
From this side of well-known discussions in philosophy and theology, an assessment is attempted to quantify the economic damages and slackening of human progress, resulting from abortions, contraceptives and unnatural behaviors. Attempts are made to evaluate the number of men and women which had not the opportunity of expressing their human characteristics, of applying their potentials and vocations in order to contribute to the progress of humanity, because their development was stopped. The production that is missing, in all activities and disciplines of human knowledge, not only from highly-gifted persons, but very much also from normal people, seems to have a greatly frightening dimension. Recent data show that the organized growth of educated populations is the solution, not the problem, for a brilliant future of humanity, by the power of the exchange of ideas, goods and organizational resources.